Law on Higher Education and Science of the Republic of Armenia: What Drove the Change? (Journal of Advanced Research in Social Sciences, 2024)
In 1991, the Soviet model of higher education in 15 republics of the USSR, with its 5.1 million students and 946 higher education institutions, started 15 independent journeys. All countries within the Soviet heritage, shared the legacies of the single Soviet approach to higher education provision: a centrally planned organization and financing, subordination to multiple sectoral ministries, a national curriculum, a vocational orientation based on the combination of strong basic education and narrow specialized job-related training, a nomenclature of types of higher education institutions, tuition-free study places and guaranteed employment upon graduation combined with mandatory job placement. After 70 years of Soviet legacy, back in 1991 Armenia initiated its independent journey. The Law on Higher and Postgraduate Education of the Republic of Armenia (RA) entered into force on April 14, 1999 and since then has undergone a number of amendments. Back in 2019 a new draft Law on Higher Education and Science was published on the Unified Website for Publication of Legal Acts’ Drafts, inviting public discussions from 03.12.2019 till 18.12.2019. Throughout two decades this was the first time when major and fundamental amendments were foreseen in the existing law on Higher and Postgraduate Education and the Law on Scientific and Scientific-Technical operations; at least this is what has been announced by the Ministry of Education, Science, Culture and Sport (MoESCS). However, the reality is that after long- lasting public discussions, debates and a lot of time spent on final version of the document, on August 2, 2021, the Constitutional Court declared the law “On Higher Education and Science” unconstitutional. This paper aims to analyze the reasons behind the proposed amendments to existing laws and the negative reception of the draft law. Specifically, it focuses on the Draft Law on Higher Education and Science, examining the historical, social, and political factors that may have influenced the agenda-setting process. Additionally, the paper employs a critical policy discourse analysis framework, with a particular emphasis on contextualization, to study the agenda-setting process.